An empirical method for reducing variability and complexity of myocardial perfusion quantification by dual bolus cardiac MRI. Issue 6 (8th September 2016) - Chatterjee, Neil; Benefield, Brandon C.; Harris, Kathleen R.; Fluckiger, Jacob U.; Carroll, Timothy; Lee, Daniel C.
Abstract : Purpose: Myocardial perfusion can be quantified using the "dual bolus" technique, which uses two separate contrast boluses to avoid signal nonlinearity in the blood pool. This technique relies on knowing the precise ratio of contrast concentrations between the two boluses. In this study, we investigated the variability found in these ratios, as well as the error it introduces, and developed a method for correction. Methods: Five dogs received dual bolus myocardial perfusion MRI scans. Perfusion was calculated separately using assumed contrast dilution ratios and empirically determined contrast ratios. Perfusion was compared with reference standard fluorescent microspheres. The same technique was then applied to a cohort of six patients with no significant coronary artery stenosis by cardiac catheterization. Results: Assumed contrast dilution ratios were 10:1 for all animal and patient scans. Empirically derived contrast ratios were significantly different for animal (8.51:1 ± 1.53:1, P  < 0.001) and patient scans (7.32:1 ± 2.27:1, P  < 0.01). Incorporating empirically derived ratios for animal scans improved correlation with microspheres from 0.84 to 0.90 ( P  < 0.05). Conclusion: Variability in dual bolus contrast concentration ratios is an important source of experimental error, especially outside of a carefully controlled laboratory setting. Empirically deriving the correct ratio is feasible and improves the accuracy of quantitative perfusion measurements. Magn Reson Med 77:2347–2355, 2017. © 2016 International Society for Magnetic Resonance in Medicine